The phytoestrogenic effect of hydroalcoholic extract of alfalfa on oxidative stress and follicle formation in adult female Wistar rats - Sajad Sistani; Mahdieh Raeeszadeh; Aliakbar Amiri (Fasa University of Medical Sciences, 2017)
Background & Objectives: Today, Infertility problems including lack of follicle formation, among other things, are of paramount importance. The aim of this study was to investigate the effect of hydroalcoholic extract of alfalfa on oxidative stress and ovarian tissue in female rats. Materials & Methods: In this experimental-interventional study, 24 rats weighing 200-250g were randomly divided into three groups: control (no treatment) and experimental groups (T1 and T2) which received alfalfa extract at 25 and 50mg/kg intraperitoneally for 25 days, respectively. Body weight of animals and their ovarian weight were measured. The left ovary was prepared for histological study. The antioxidant capacity in serum and malondialdehyde in right ovary extracts were also measured. Results: At the end of the study, the body weight of the animals in both control and experimental groups compared to that of pre-intervention time, but the increase was not statistically significant (P>0.05). The most ovarian weight was observed in T2group (160g) and the lowest weight was in the control group (146g). The primary and secondary follicles and corpus luteum were the highest number in the T2group of alfalfa extract and the lowest number in the control group. The serum antioxidant capacity in T1 and T2groups were about 922 and 937µmol/ml, respectively, and the lowest amount was in the control group with 780µmol/ml and the difference was significant. Malondialdehyde concentration in control and T2gruop were the average of 0.35 and 0.22µmol/ml, respectively (P<0.05). Conclusion: Hydroalcoholic extract of alfalfa with phytoestrogenic and oxidative stress control effects can enhance ovarian activity in adult rats.